PUBLIC COMMUNICATION STRATEGIES TO INCREASE COMMUNITY TRUST IN FIGHTING OFF COVID-19 INFODEMIC (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2021)
At the moment, the government is not only trying to tackle the problem of the global Covid-19 pandemic, but is working hard to suppress the infodemic, namely the flood of false information and disinformation about the Covid-19 virus that is spreading massively in the digital space. The occurrence of confusion about information regarding the Covid-19 virus is the goal in this study by looking at the implementation of public communication strategies that have been carried out by the government in conveying effective messages clearly and comprehensively in efforts to overcome the Covid-19 pandemic infodemic in Indonesia. This research is focused on disinformation and fake news about Covid-19 that has been circulating massively in the digital space. The method used is a literature study sourced from journals, various reports in online media, and relevant documents. The results and conclusions showed the public communication strategy carried out by the government, namely by making a public communication timeline by the Directorate General of Information and Public Communication, a socialization program that was adapted to current policies and distributed through digital government channels, the aduankonten.id page facility for the public to report negative content, forming a special spokesperson for the implementation of the Covid-19 vaccination, and technical guidelines for public communication protocols to increase public confidence in the government's performance. The obstacles faced by the government, there are anomalies in public communications, inaccurate data and information, low levels of public trust in the government, and regulations that are not clear and firm. Keywords: Communication Strategies, Infodemic, Hoax Covid-19